Głos w dyskusji o tekście staropolskim. Znad kanonów mszy św. - Dorota Masłej (Ksiegarnia Akademicka Publishing, 2017)
A Contribution to the Discussion on Old Polish Text. Analysing the Canons of the Mass The paper analyses selected mediaeval Canons of the Mass from a text linguisctic perspective. It focuses on four monuments which are considered glosses from the point of view of the formal criterion (the placement on the page), and texts from the point of view of their shape (the degree of development). The analysis includes the graphical shape of the annotations, the syntax of the Polish passages with respect to the Latin prototype, the base and the completeness of the translation. This multi-faceted analysis leads to the conclusion that mediaeval Polish glosses to the Canons of the Mass consitute not a text but a complete collection of glosses. This conclusion is justified by both their graphical and grammatical shape: verbatim rendering of Latin constructions and inflections (inconsistent with Polish grammar), and accumulation of multiple lexical equivalents of a single element. When working with this kind of monuments, one needs to take into account not only the quantitative criterion (completeness of the translation) but also the function of the whole that the scribe created, and the intention of the author.